Schur Test for the Hardy Operator - Berezhnoi, Evgenii Ivanovich (Eurasian Mathematical Journal, 2013)
For monotonic functions necessary and sufficient conditions are investigated ensuring the equivalence of a function and of an integral containing that function. Factorization theorems (Schur tests) are proved for the classical Hardy operator and its adjoint in Lebesque spaces with monotonic weights.